Wnt/β-catenin signalling modulates the timing of cell fate decision making in the early mouse embryo - Joaquin Lilao-Garzón; Elena Corujo-Simon; Meritxell Vinyoles; Sabine C. Fischer; José Guillén; Tina Balayo; Silvia Muñoz-Descalzo (PLoS ONE, 2026)
Cell fate choice is a key event happening during preimplantation mouse development. From embryonic day 3.5 (E3.5) to E4.5, the inner cell mass (ICM) differentiates into epiblast (Epi, NANOG expressing cells) and primitive endoderm (PrE, GATA6, SOX17 and/or GATA4 expressing cells). The mechanism by which ICM cells differentiate into Epi cells and PrE cells remains partially unknown. FGF/ERK has been proposed as the main signalling pathway for this event, but it does not explain co-expression of NANOG and GATA6 or how the cell fate choice is initiated. In this study, we investigate whether Wnt/β-catenin signalling also plays a role. To this end, we use two in vitro models based on inducible GATA6 expression: one in 2D (flat cultured cells), and another in 3D, namely ICM organoids. By combining these in vitro models with in vivo mouse embryos, chemical and classical genetics, and quantitative 3D immunofluorescence analyses, we propose a dual role for Wnt/β-catenin signalling. We find that β-catenin, acting alongside FGF/ERK signalling, helps to guide the cell fate choice towards PrE. Additionally, by regulating GATA6 and GATA4 stability, Wnt/β-catenin signalling further facilitates this choice. To summarise, we observe that Wnt/β-catenin signalling pathway activation promotes PrE differentiation, while its inhibition delays it.